Сучасний стан популяцій рідкісних видів степових угруповань Волинської височини - Logvynenko, I.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The article contains results of monitoring researches (2008–2011) as the positions of rare species populations of steppe groups Volyn Upland. It is determined the current situation of populations Carlina onopordifolia Bess. ex Szaf., Kulcz. et Pawl., Adonis vernalis L., Trifolium rubens L., Cerasus fruticosa (Pall.) G. Woron and emphasiged the main factors that negatively affect them.